The Influence of Knowledge, Attitudes, and Skills of Malaria Microscopists on the Accuracy of Laboratory Diagnosis Results - Sahli, Indra Taufik; Wirawan, Chevie; Kawaitouw, Leberina; Kosasih, Kosasih; Asrianto, Asrianto (Baiman Bauntung Batuah Center, 2024)
Malaria remains a significant public health issue in Indonesia, characterized by high rates of illness and death. Proper laboratory diagnosis is one of the keys to malaria prevention efforts. Malaria microscopists' proficiency, knowledge, attitudes, and skills require regular assessment to maintain diagnostic quality. This study examines the correlation between malaria microscopists' knowledge, attitudes, and competencies and the accuracy of laboratory diagnostic outcomes at the Jayapura City Health Center. This study used quantitative methods with descriptive and verification approaches. Data were collected through questionnaires and laboratory diagnosis results. The study sample was 13 malaria microscopists at the Jayapura City Health Center. The data were analyzed with SPSS software. The results showed that most respondents had a good level of knowledge (76.9%). Almost half of the respondents had a good attitude (46.2%). Most respondents had a sufficient level of skill (61.5%). Interestingly, although most respondents (76.9%) could diagnose malaria very accurately, this study did not find an effect of malaria microscopists' knowledge, attitude, and skills on the accuracy of diagnosis. The knowledge level of malaria microscopists at the Jayapura City Health Center is good, but their attitudes and skills still need to be improved. It is recommended that microscope Officers routinely attend training to improve their knowledge, attitudes and skills.